MANAGEMENT OF AGRICULTURAL ECOSYSTEM FROM DETRIMENT AREA. CASE OF STUDY – BACĂU - Bran, Mariana; Dobre, Iuliana; Voicu, Radu (Economics of Agriculture, 2008)
At present, the agriculture is under the impact of a new type of economy and European structures integration. Therefore, agriculture must be approached as an important branch of the national economy but also because people must eat and because self-agrifood and positive comercial balance are promoted in the world. So, principles of market economy must be followed including constant modifications during reform of agricultural economic base. To achieve that, it is necessary to adopt new laws in agriculture, to conduct modernisation of rural infrastructure and to protect ecosystem through preservation and improvement of agrifood chain functionality.